Empathetic Storytelling, Volume I - Murawska, Jaclyn; Nank, Sean (Critical Storytelling, 2024)
In the Critical Storytelling series, this latest book elevates the voices of a myriad of authors using empathetic storytelling to ignite change in education. Stories connect us through the meaning we make, intricately woven in a diverse tapestry of shared experiences held together with the delicate thread of our humanity. Uncovering implicit biases and choices inherent in the two themes of all -isms (including racism, sexism, and ableism) and bullying, the editors offer concrete strategies for classroom teachers, professors, educational leaders, and policy makers to use storytelling to complement awareness and discourse with calls to action. Contributors are: Katey Arrington, Liza Bondurant, Reginald E. Duncan, Emma Funderburk, Tamun Hanjra, Carlos LópezLeiva, Jaclyn Murawska, Sean Nank, Keiran Nank, Leigh-Anne Peper, Nikki Pitcher, Gayle Richardson and Michael D. Steele.